Prevalence of prehypertension and its association with body mass index among the medical students - Bhaila, Archana; Shakya, Binnam; Nepal, Grishma Banskota; Shrestha, Hari Sunder; Maharjan, Niroj; Adhikari, Bijaya (Journal of Chitwan Medical College, 2021)
Background: Prehypertension in adolescents is an important risk for developing hypertension in later years of life. Hypertension is one of the major cardiovascular problems in urban and suburban areas of Nepal and is increasing among the young population. There are not many studies reported in Nepal which estimates the prevalence of hypertension among medical students. Hence, this study aimed to assess the prevalence of prehypertension and its association with body mass index so that it would assist in developing strategies for control of hypertension and cardiovascular diseases in later years of life Methods: This cross-sectional study included 250 medical students. Anthropometric variables of the subjects were recorded. Height and weight were measured on calibrated scales and body mass index was calculated. Waist and hip measurements were obtained and waist-hip ratio was calculated. Blood pressure was measured with a mercury sphygmomanometer. The data obtained was divided into different groups according to blood pressure and BMI. Descriptive statistics, chi-square test was used for presenting data and testing the significance and P<0.05 was considered as statistically significant. Results: The prevalence of normotensive, prehypertensive and hypertensive students was found to be 75.2%, 20.8% and 4% respectively. Mean BMI was found to be 21.59±3.39. In general, 75.2% of the students had ideal waist hip ratio, 15.2% were underweight, 70 % had normal weight, 12 % were overweight, and 2.8% were found to be obese. Moreover, 51.4% of prehypertensives had BMI more than 25. Prehypertension was significantly higher among males (χ2=16.385, p<0.001) and among the obese medical students (χ2=16.416,p<0.001). Conclusions: Prehypertension is prevalent in about a third of medical students and BMI is found to be significantly associated with pre-hypertension.